The hybrid victim: Re-conceptualizing high-tech cyber victimization through actor-network theory: - Wagen, Wytske van der (European journal of criminology, 2020)
Victims are often conceptualized as single, human and static entities with certain risk factors that make them more vulnerable and attractive for offenders. This framework is challenged by emerging forms of high-tech cybercrime, such as ransomware, botnets and virtual theft, in which the offender targets a composite of human, technical and virtual entities. This study critically assesses the current theorization of the cyber victim and offers an alternative approach. Drawing on actor-network theory and three empirical case studies, it analyses the cyber victim as a hybrid actor-network consisting of different entities that, together with the offender, make the victimization possible. The proposed concepts of victim composition, delegation and translation enable a more profound understanding of the hybrid and complex process of becoming a high-tech cyber victim. Keywords: cybercrime, cyber victimization, actor-network theory, botnet, ransomware, virtual theft